STRATEGIES USED IN THE TRANSLATION OF THE WIZARD AND THE HOPPING POT BY J.K. ROWLING - Sabrina, Adani Nur (Universitas Gunadarma, 2021)
The world of literature is always evolving from time to time, and for the sake of these works to be evenly shared throughout the globe, the role of translator is needed. In order to observe how a literary work is translated, this research discusses a bedtime story entitled The Wizard and the Hopping Pot written by J.K. Rowling and its translation by Nina Andiana and Listiana Srisanti, Sang Penyihir dan Kuali Melompat. The purposes of this research are to find out what strategies are used in the translation, as well as to evaluate the translation’s accuracy, clarity, and naturalness to the readers. The method used is descriptive qualitative which means the data are analyzed and discussed in the form of sentences. The result shows that there are forty-seven data found which include nine different translation strategies namely transposition, unit shifts, cohesion change, scheme change, distribution change (expansion and reduction), hyponymy, explicitness change (implicit to explicit and explicit to implicit), information change, and coherence change. By conducting this research, the researcher implies to provide more translation strategies and evaluations so that the researcher and also the readers in general can use it whenever they find difficulties in doing any translation.